Penerapan Asuhan Keperawatan Berdasarkan Self Transcendence Theory Pamela G.Reed - Elsmin Tri Yulyana Kiayi; Irna Nursanti (Protein : Jurnal Ilmu Keperawatan dan Kebidanan., 2024)
Nursing care is a process or series of activities in nursing practice that is provided directly to clients/patients in various health service settings. In implementing nursing care based on self-transcendence theory, nurses play the role of facilitators to help individuals experience growth and development through the self-transcendence process. Self-transcendence theory was developed by Pamela G. Reed and emphasizes the spiritual and transpersonal aspects of treatment. Reed explained that nurses act as facilitators to explore positive things and build bio-psycho-social spiritual well-being. Self Transcendence Theory aims to understand a person's movement in transcending self-limitations and achieving higher well-being. This theory focuses on five concepts, namely vulnerability, self-transcendence, well-being, moderating-mediating factors, and point of intervention. This self-transcendence offers the best for living in peace and prosperity. Apart from that, this theory is also used in the context of counseling services to help individuals utilize inner resources that empower patient capacities. Thus, the aim of the Self Transcendence theory is to understand and encourage individuals to achieve higher well-being through holistic self-understanding and development.